An Analysis of the relationship between exports and economic growth - SANN, Thi Lwin (KDI School, 2017)
This study analyzes the impacts of the exports on the economic growth for the period 1990-2015 by using annual data of GDP, Exports, Imports and FDI in Myanmar. The main objective of this study is to determine whether the exports have positive or negative effects on the economic growth. Autoregressive Distributed Lag (ARDL) Model is mostly used to observe the relationship among exports and economic growth. This study used the ADF test to check the unit root of the time series and all variables are stationary at first differencing level (except FDI which is stationary in the level). The residual normality test, heteroskedacity and serial correlation tests are used to check diagnostic tests. This model also checked the stability by CUSUM test. The ARDL model describes a statistically significant long-run positive relationship between exports and gross domestic product in Myanmar. Moreover, this study finds that exports and FDI have positive effects on the economic growth while imports have positively insignificant in the long-run. As a policy implication, this study suggests that the government should focus on economic stability, new SMEs capabilities and openness policy within the country.
Thesis(Master) --KDI School:Master of Public Policy,2017